Soluble polybenzimidazoles with intrinsic porosity: Synthesis, structure, properties and processability. Issue 10 (16th February 2018) - Kumar, Vikas; Chatterjee, Shyambo; Sharma, Pragati; Chakrabarty, Suman; Avadhani, Chilukuri V.; Sivaram, Swaminathan
ABSTRACT: We have explored two novel comonomers, namely, 4, 16‐dicarboxyl[2.2]paracyclophane and 5, 5′, 6, 6′‐tetraamino‐3, 3, 3′, 3′‐tetramethyl‐1, 1′‐spirobi[indane], for the synthesis of co‐polybenzimidazoles (co‐PBIs) with intrinsic porosity. Both these monomers possess twisted structures that can lead to "awkward" macromolecular shapes that cannot pack efficiently. The consequences of introducing these two monomers on the structure and properties of PBIs are reported. The random copolymers synthesized are amorphous and possess glass transition temperatures ( T g s) greater than 400 °C. T g decreases with increasing comonomer content indicating an increase in fractional free volume. The copolymers have low surface area. TEM and BET measurements show evidence of mesopore formation. The copolymers show significant carbon dioxide adsorption. Single chain molecular dynamics simulation of 24‐mer repeat units shows intramolecular void spaces arising as a result of distorted polymer chain with reduced conformational mobility. These studies define a new synthetic strategy for "bottoms‐up" synthesis of PBIs with intrinsic porosity. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 1046–1057 Abstract : Soluble porous polybenzimidazoles (PBIs) based on rigid and contorted monomers, namely, 4, 16‐dicarboxyl[2.2]paracyclophane and 5, 5′, 6, 6′‐tetraamino‐3, 3, 3′, 3′‐tetramethyl‐1, 1′‐spirobi [indane] were synthesized. Comonomer (10 mol %) insertion resulted in soluble PBIs. Amorphous PBIs exhibited high glass transition temperatures and thermal stability. HR‐TEM and BET provide evidence of porosity. The basic nature of imidazole promoted carbon dioxide absorption. Molecular dynamic simulations indicate that cyclophane and spirobisindane monomers result in structures with large intramolecular voids. This method provides a "bottoms‐up" approach for the synthesis of soluble mesoporous PBIs.